The Influence ROA, ROE, NPM, EPS and PER to Market Price on Public Listed Manufacture of Food Products 2018-2022 - Mila Hiswatus Sholihah; Heru Tjaraka (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
This study aims to provide empirical evidence in financial ratios which include ROA, ROE, NPM, EPS and PER for significance in predicting market prices on public listed food manufacture of food products in the 2018-2022 to minimize information asymmetry, increase transparency and accuracy between management and stakeholders that occur in a stock market. The research samples in this study are public food manufacturing companies in Indonesia in 2018-2022. This study uses panel data with cross-sectional data for 45 companies and time series data from 2018-2022. The total sample in this study is 201 samples. The results of this study indicate that H1 ROA has no significant effect on market price. Meanwhile, H2 ROE, H3 NPM, H4 EPS and H5 PER have a significant effect on market price